Differences in soil evaporation between row and interrow positions in furrowed agricultural fields. Issue 1 (8th December 2020) - Al‐Oqaili, Firas; Good, Stephen P.; Frost, Kenneth; Higgins, Chad W.
Abstract: Although large‐scale center pivot sprinkler irrigation has replaced surface irrigation in many locations, the agricultural practice of growing crops in furrows remains common. Still, how the presence of elevated soil rows under sprinkler irrigation influences evaporation losses remains unclear, even while quantifying nonproductive water losses becomes increasingly important for informing new water conservation and irrigation strategies. In this study at the Hermiston Agricultural Research and Extension Center in Hermiston, OR, soil evaporation from the row and interrow positions within potato ( Solanum tuberosum L.) fields of contrasting irrigation timing (daytime vs. nighttime) was estimated based on hydrogen and oxygen isotope ratios. Samples collected throughout the 2016 growing season were analyzed and used to calculate soil evaporation ( E ) losses relative to applied irrigation ( I ). On average, row positions were more enriched in heavy isotopes than interrow positions, indicating that the evaporated fraction of applied irrigation ( E / I ) depends on the position. Within the day‐irrigated field, the estimated (mean ± standard deviation) E / I ratios determined from both stable isotopes for May, July, and September were 18 ± 8%, 10 ± 3%, and 19 ± 5% for row and 15 ± 6%, 7 ± 2%, and 12 ± 4% for interrow samples. Within the night‐irrigated field during these same months, the E / I ratios were 13 ± 12%, 16 ± 7%, and 13 ± 5% for row and 12 ± 7%, 9 ± 2%, and 6 ± 2% for interrow samples, respectively. For these fields, these results reveal that there is more evaporation from row, as compared with interrow, positions. Therefore, management practices for water conservation should account for larger nonproductive evaporation from within rows in order to minimize evaporative losses. Core Ideas: Irrigation timing did not significantly influence the surface soil moisture content. Significant differences in soil isotopes were found between locations. Row locations experience more evaporation than interrow spaces.